The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/joc.5703
|View full text |Cite
|
Sign up to set email alerts
|

Dominant modes of wintertime precipitation variability in northwest China and the association with circulation anomalies and sea surface temperature

Abstract: The dominant modes wintertime precipitation in northwest China (NWC) and the possible causes are investigated during the period 1961-2013 in the inter-annual timescale, as winter climate condition could greatly affect local economic development and people's lives. The analysis of this study is divided into three parts. First, the spatiotemporal variability of dominant modes wintertime precipitation is described by an empirical orthogonal function (EOF) method. The atmospheric circulation anomalies associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…For period 1961-2013, positive SSTA appear in the tropical eastern-central Pacific (Fig. 2a), indicating a positive connection between NWC WP and the El Niño events, consistent with our previous study (Yin and Zhou 2018). However, note that the intensity of the SSTA is not very strong, which may imply an interdecadal change in the relationship (Figs.…”
Section: Interdecadal Change In the Relationships Between Nwc Wp And supporting
confidence: 91%
See 2 more Smart Citations
“…For period 1961-2013, positive SSTA appear in the tropical eastern-central Pacific (Fig. 2a), indicating a positive connection between NWC WP and the El Niño events, consistent with our previous study (Yin and Zhou 2018). However, note that the intensity of the SSTA is not very strong, which may imply an interdecadal change in the relationship (Figs.…”
Section: Interdecadal Change In the Relationships Between Nwc Wp And supporting
confidence: 91%
“…The NWC WP is defined as the leading mode of NDJFM precipitation of the 130 stations (dots in Fig. 1a) located to the west of 1108E and to the north of 358N in China obtained using the empirical orthogonal function (EOF) method, following Yin and Zhou (2018). The Niño-3.4 SST (58S-58N, 1708-1208W) is used as an index for ENSO.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The uniform change in winter precipitation over NWC in the late 1980s represents the leading EOF mode of NWC winter rainfall anomalies (Yin and Zhou, 2018). However, some studies have suggested an opposite change in winter precipitation in the western and eastern areas of NWC (e.g., Song and Zhang, 2003).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Understanding precipitation variability as well as its association with teleconnections is beneficial for a better adaptation to varying climatic conditions and a reduction in the damage related to climate change. The annual and interannual-to-decadal teleconnections (or oscillations) are often regarded as two of the most notable patterns and explanatory variables of climatic and hydrological variability (e.g., Hua et al, 2019;Lee et al, 2018;Li et al, 2018;Murgulet et al, 2017;Yin & Zhou, 2018). Valdés-Pineda et al (2018) adopted Singular Spectrum Analysis techniques to analyze the combined influence of two teleconnections on the variability of monthly precipitation in Chile.…”
mentioning
confidence: 99%